The Effect of Retrieval Focus and Emotional Valence on the Inferior Frontal Cortex Activity during Autobiographical Recollection - Denkova, Ekaterina; Dolcos, Sanda; Dolcos, Florin (Frontiers in Behavioral Neuroscience, 2013)
Although available evidence points to a role of the inferior frontal cortex (IFC) in both emotion processing and autobiographical memory (AM) recollection, it is unclear what the role of this region is in emotional AMs recollection. The present study investigated whether IFC activity can be influenced by manipulations of the retrieval focus (emotional vs. non-emotional) and whether this influence is similar for AMs with positive and negative emotional valence. Participants were asked to focus either on emotional (Emotion condition) or on non-emotional contextual (Context condition) details during the elaboration of positive and negative AMs, while fMRI data were collected. The study yielded two main findings: (1) Focusing on emotion compared to context during AMs recollection was associated with increased activity in bilateral IFC, for positive AMs, whereas negative AMs produced similarly high IFC activity during Emotion and Context conditions; (2) There was a hemispheric dissociation in the IFC linked to the experiencing of emotion and the focus of AM Recollection, such that the left IFC activity correlated positively with the subjective re-experience of emotion during the Emotion condition, whereas the right IFC activity correlated negatively with the subjective re-experience of emotion during the Context condition, for both positive and negative AMs. Overall, the present findings suggest that IFC’s involvement during the recollection of emotional AMs is susceptible to manipulations of the retrieval focus only in the case of positive AMs, and that this region plays a role in both the enhancement and inhibition of emotional experience during AM recollection.